Analisis SWOT dalam Studi Kelayakan Bisnis Produk Reseller Hijab - Cahyadi, Cahyadi; Murdiono, Deden; Faizal, Rizki Ahmad; Azis, Rizqi Muhamad Abdul; Endriansyah, Bintang Rama; Aristri, Alamsyah Putra; Siregar, Ronal Benyamin; Saputra, Dodi Eka; Nurmanda, Yunengsih; Mutiara, Adinda (Proceeding Mercu Buana Conference on Industrial Engineering, 2025)
The purpose of writing this article is to understand and analyze the SWOT of hijab reseller products. This type of research uses qualitative descriptive research methods and the type of data uses empirical data or personal experience. The result of this research is to provide opportunities or conveniences for everyone who wants to start a business but has little capital to become a reseller. In addition, entrepreneurs can understand resellers through the analysis of strengths, weaknesses, opportunities, and threats that can serve as a guideline for their business. This SWOT analysis provides positive effects such as offering a perspective on primary priorities, recognizing risks, constraints, problems, and threats that may occur, helping to develop businesses, and facilitating decision-making.